Organic Reactions 2011
DOI: 10.1002/0471264180.or007.02
|View full text |Cite
|
Sign up to set email alerts
|

TheSkraup Synthesis of Quinolines

Abstract: Konigs first synthesized quinoline in 1879 by passing allylaniline over heated litharge. Shortly after he prepared quinoline by heating the condensation product of aniline and acrolein, thus anticipating the classical Skraup synthesis. This synthesis involves a series of reactions brought about by heating a primary aromatic amine, in which at least one position ortho to the amino group is unsubstituted, with glycerol, sulfuric acid, and an oxidizing agent. The product is a quinoline containing only those subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 227 publications
0
30
0
3
Order By: Relevance
“…Simultaneouly, the nitro group was reduced to amino group. This intramolecular oxidation-reduction was similar to Skraup reaction, in which nitrobenzene served as the oxidizing agent to remove the hydrogen of dihydroquinoline and itself was reduced to aniline [25]. However, the reaction of 1c and 3-AT afforded the normal product 2c, which is of interest for further investigation.…”
Section: Chemistrymentioning
confidence: 83%
“…Simultaneouly, the nitro group was reduced to amino group. This intramolecular oxidation-reduction was similar to Skraup reaction, in which nitrobenzene served as the oxidizing agent to remove the hydrogen of dihydroquinoline and itself was reduced to aniline [25]. However, the reaction of 1c and 3-AT afforded the normal product 2c, which is of interest for further investigation.…”
Section: Chemistrymentioning
confidence: 83%
“…(11)) [148] Various types of quinolines have been synthesized for application to pharmaceuticals, dyes, and feed additives. The Skraup synthesis is of great general utility and has been applied to many aromatic amines combined with glycerol or acrolein [149], because the route is straightforward, readily available starting material are used, and the procedure is simple. Reaction of aniline with acetone to yield 1,2-dihydro-2,2,4-trimethylquinoline is a modification of the Skraup synthesis, in which strong acids (pKa < 2) or halogens are used as the catalyst.…”
Section: Alkylation With Estermentioning
confidence: 99%
“…A great deal of investigation has previously shown that the possible formation of 5-and 7-substituted quinolines during the well-known Skraup reaction with m-substituted anilines involves conflicting reports about the composition of the products from certain reactions (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%